ANALISIS KEPUASAN PETANI TERHADAP KINERJA PELAYANAN PEMERINTAH DALAM PENGEMBANGAN AGRIBISNIS JAGUNG MANIS DI KOTA PEKANBARU - Bina Presty Dokta; Rosnita '; Novia Dewi (Fakultas Pertanian, Universitas Riau, 2015)
Sweet corn is an important commodity in Pekanbaru,where its production is still low, which reached 379,45 tons while its demand is 12.571,12 tons. During this,sweet corn are stillimported from outside theregion such as West Sumatra and North Sumatra to cover the gap needs of the community.Various efforts and programs have been made by the government to overcome obstacles and meet the needs of farmers in developing sweet corn commodity in Pekanbaru.In order for the implementation of the sweet corn agribusiness development program in Pekanbaru run effectively, it is important to know what are the needs of farmers, government efforts, and the level of satisfaction of farmers on government services for these, so known that the performance of the variable service should be corrected by the government in the future. Research on 137 sweet corn farmers scattered in two sub-districts in Pekanbaru. The analytical method used were descriptive analysis, IPA (Importance Performance Analysis) dan Gap Analysis on four subsystems agribusiness. The results, that was using Likert Scale's Summated Rating (SLR), illustrates that low levels of farmers satisfaction on the performance of government services for the following reasons : the type and amount of agricultural inputs assistance from government were not suited to the needs of farmers for planting once, lack of the role of extension,lack of government support in the processing and marketing of sweet corn.